2021
DOI: 10.36740/wlek202110123
|View full text |Cite
|
Sign up to set email alerts
|

Features of Hemodynamics in Head Magistral and Cerebral Arteries in the Patients With Migraine

Abstract: The aim of the study was to Doppler sonography study of the structural and functional state of head magistral arteries (HMA) and cerebral arteries in the patients with various forms of migraine. Materials and methods: We conducted the clinical Doppler examination of 124 young patients (18-45 years old), including 55 men and 69 women in the conditions of the clinical base of the Kharkiv Medical Academy of Postgraduate Education in 2017-2019. The criteria for involvement of patients in the study were: migraine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…17,23 The present study results did not demonstrate a significant difference in the PSV within the ECA, between active migraines and symptom-free intervals. This was in contrast with the findings by Kalashnikov et al 29 that showed significantly lower velocity of the artery during active headaches.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…17,23 The present study results did not demonstrate a significant difference in the PSV within the ECA, between active migraines and symptom-free intervals. This was in contrast with the findings by Kalashnikov et al 29 that showed significantly lower velocity of the artery during active headaches.…”
Section: Discussioncontrasting
confidence: 99%
“…In most of the abovementioned studies, only a few extracranial arteries were studied. [22][23][24][25][26][27][28][29][30] Given the fact that migraine is a debilitating disease, which can significantly reduce the quality of life, especially among teenagers and young people, the objective was to assess vertebral arteries, superficial temporal arteries, ICAs, external carotid arteries (ECAs), and common carotid arteries (CCAs) of patients with migraine disease, using sonography. By comparing the diameter of arteries, pulsatility index (PI), resistive index (RI), and peak systolic velocity (PSV), during migraine headache attacks and nonheadache intervals, the aim was to gain a better understanding of the vascular changes during active headaches.…”
mentioning
confidence: 99%